Economic Welfare on Justice, Faith And Blessing Based on The Qur'anic Perspective - Ian Alfian; Azhari Akmal Tarigan; Rahmi Syahreza; Ahmad Riyansyah Parinduri (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2024)
This research discusses the relationship between faith, justice, and blessings in achieving economic welfare from an Islamic perspective. Using the conceptual study method, this research relies on primary sources in the form of tafsir books by Rafiq Yunus Almasri, Muhammad Ghazali, Johan Efendi, and Quraish Shihab, as well as secondary sources from articles discussing economic welfare from an Islamic perspective. The analysis results show that faith serves as a spiritual foundation that encourages the application of justice principles in economic transactions, while blessings reinforce the success of achieving sustainable prosperity. Additionally, applying Islamic principles in daily life has proven important for creating sustainable social and economic justice. This research also found hope in raising awareness among Muslims about the importance of justice, faith, and blessings in the context of the modern economy to drive positive change and strengthen the overall quality of life in society. Thus, integrating Islamic teachings into the economy is expected to create a prosperous and just society.